PENELITIAN PENERAPAN TEKNOLOGI INFORMASI DI PERPUSTAKAAN MELALUI DATABASE GOOGLE SCHOLAR: : NARRATIVE LITERATURE REVIEW - Farabi, Muhammad Nabiel (VISI PUSTAKA: Buletin Jaringan Informasi Antar Perpustakaan, 2024)
The purpose of this research is to conduct a literature review or narrative review regarding the application of information technology in libraries through the use of the Google Scholar database. The method used includes searching for scientific articles related to the application of information technology in libraries using the Google Scholar database. In the search process, articles were selected based on inclusion and exclusion criteria, such as language (English and Indonesian), publication period (2013–2022), and focus on the application of information technology in libraries. The results of this study indicate that the application of information technology in libraries has an important role in increasing the efficiency and effectiveness of library services. Some examples of information technology that have been implemented in libraries include library management systems, digitization of library collections, library portals, RFID, and self-checkout kiosks. The application of information technology assists libraries in managing collections, lending books, extending loan periods, and facilitating user access to library collections. However, this study also identified some of the challenges faced in implementing information technology in libraries, such as limited funds for information technology procurement, the limited skills or expertise of library staff in managing information technology, and user data security. Therefore, the conclusions of this study emphasize the importance of good management and maintenance of information technology and improving the skills and expertise of library staff in managing information technology in order to maximize the benefits of implementing information technology in libraries.